Effectiveness of the Student Entrepreneurship Development Program at Muhammadiyah University of Sidoarjo: Efektivitas Program Pembinaan Mahasiswa Wirausaha di Universitas Muhammadiyah Sidoarjo - Bayu Hari Prasojo; Mohammad Alim Ahaddin; Dwi Maya Rahmawati (Academia Open, 2022)
This study purposed was to determine the effectiveness of the Entrepreneurial Student Developmen Program at Universitas Muhammadiyah Sidoarjo. This study used qualitative descriptive research type. Data collection techniques using the method of observation, interviews, and documentation. Data analysis techniques using data reduction steps, data presentation, and conclusions. The results showed from the indicators of measuring the effectiveness of Understanding of the program shows that the higher education implementers understand their duties and responsibilities in accordance with their respective main tasks and functions, besides that students also understand what requirements are needed in managing student entrepreneurship. Right on target, it can be said to be effective in achieving predetermined targets, namely being able to exceed the target of the Key Performance Indicators (IKU), namely forming entrepreneurs who have business legality.Timeliness, shows that it is said to be effective because from the start the activity, implementation and reporting went according to a predetermined timeline. The achievement of the goals went well, this can be seen in the program achievements, starting from product development, human resource development and managing business legality from the student entrepreneur implementing team.Real Change, said to be effective, can be seen in being able to make entrepreneurial opportunities for students, having confidence in carrying out entrepreneurship, expanding market reach and the addition of business profits earned. By fulfilling the above effectiveness indicators, the Student Entrepreneurial Development Program (P2MW) at the Universitas Muhammadiyah Sidoarjo runs effectively. Highlights: Understanding and fulfillment of program requirements by higher education implementers and students. Achievement of predetermined targets, including exceeding Key Performance Indicators (IKU) and forming entrepreneurs with business legality. Timely implementation, reporting, and successful goal achievement, leading to real change in entrepreneurial opportunities, student confidence, market reach, and business profits. Keywords: Entrepreneur, Student, Development Program, Effectiveness, Universitas Muhammadiyah Sidoarjo